Exploring the Potential of Internal Information Flows in Large Organizations as Leverage Points for Environmental Stewardship. Issue 1 (2nd January 2023) - Farhad, Sherman; McGlynn, Bridget; Baird, Julia; Plummer, Ryan; Blythe, Jessica
Abstract: Large organizations play a critical role in environmental stewardship. The concept of leverage points offers one promising avenue of inquiry to enhance the effectiveness of large organizations in advancing environmental stewardship. Here, we focus on the flow of information within a large environmental organization as a deep leverage point for system change. We conducted a social network analysis of an organization with an environmental stewardship mandate. Results show that the organization has a dense communication network that could be effectively leveraged for environmental stewardship communication, especially by influential individuals and departments. As practical implications, we recommend that an environmental stewardship-focused communication approach, based on four strategies (segmentation, induction, two-way communication, and individual strategies) be enacted by the organization to use this leverage point to enhance the diffusion of environmental stewardship. Directions for future research include a deep study of the plurality of understandings of environmental stewardship within the organization.